Learning Strategies at SD Muhammadiyah 2 Tulangan during the Covid 19 Pandemic - Lintang Nimas Primaningtyas; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The study aims to analyze the learning process in the (online) network, supportive factors and teacher inhibitory factors in carrying out online learning during the covid-19 pandemic. The study was carried out at muhammadiyah elementary school 2 the estimated shidoarjo city of sidoarjo in April. The study USES descriptive qualitative methods. The subject used in this study was an elementary school teacher at 2 tulangan elementary elementary school. The data-collection techniques used in this study include interviews, documentation and field notes. The result of this study is that the covid-19 pandemic has hada profound impact on the learning process, learning that is normally executed directly is now being transferred to online learning. Learners are bored and bored during learning. Online education done for primary-age children is less effective. A number of teacher factors in the online learning process are the availability of cell phones, quotas and a steady Internet network. In addition to supporting factors in online learning, there are several teacher inhibitors in online learning. These inhibiting factors include the fact that they are still at the elementary school level, so only a few students have cellphones, therefore this can make learning ineffective. Through online there are also obstacles that occur for teachers, namely many students who deliberately do not participate in online learning because they do not have an internet quota to access learning so that students are left behind. And there is also a learning strategy carried out by SD Muhammadiyah 2 Tulangan. On the other hand, face-to-face online learning through applications is the most beneficial thing to break the spread of Covid-19 and maintain the mental health of teachers and students from exposure to the Covid-19 virus.